Negative electrode active material, secondary battery comprising same, and electronic device
By forming coated secondary particles composed of the first phase and the second phase material in the negative electrode material of the lithium-ion battery and reserved an appropriate amount of pores inside it, the problem of insufficient electrical performance of the negative electrode material in the existing lithium-ion battery is solved, and higher energy density and cycling stability are achieved.
Patent Information
- Application Number
- CN202411929571.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-25
AI Technical Summary
In the existing lithium-ion batteries, graphite has a high degree of crystallization as the negative electrode material and has poor compatibility with the electrolyte, which leads to a low diffusion rate of lithium ions, making it difficult to meet the electrical performance requirements at high magnifications.
By combining the first phase material and the second phase material, secondary particles are formed covering the surface of the first phase material, and pores are reserved inside the particles, and the percentage of pore area is controlled in the range of 0.5% to 35%, so as to improve the contactability and cyclic stability of the material.
The electrode sheet resistance is reduced, the compaction density of the active material is improved, the energy density and circulation performance of the secondary battery are enhanced, and the volume expansion of the material during circulation is alleviated.
Smart Images

Figure CN119695124A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of electrochemical technology, and in particular to a negative electrode active material, a secondary battery containing the negative electrode active material, and an electronic device. Background Art
[0002] Lithium-ion secondary batteries have become the focus of research in the field of new energy due to their high energy density, stable charge and discharge platform, low self-discharge rate, and long cycle life. The negative electrode active material in lithium-ion batteries is a key factor affecting battery performance. It is one of the four main materials in the battery system and accounts for 5%-15% of the battery cost. At present, the commercial negative electrode material is mainly graphite, including natural graphite and artificial graphite, but graphite has a high degree of crystallization, poor compatibility with electrolytes, and a low diffusion rate of lithium ions between layers, resulting in poor electrical performance of graphite at high rates, which is difficult to meet people's increasingly high requirements for electrochemical devices.
[0003] Hard carbon materials have attracted great attention due to their high theoretical capacity, low volume expansion, and fast charge and discharge. In 1991, Sony Corporation of Japan first developed a lithium-ion battery using polyfurfuryl alcohol pyrolysis carbon as the negative electrode material. In hard carbon materials, lithium ions can be embedded and extracted from all angles, with excellent rate performance and cycle characteristics. However, the low compaction density and first coulomb efficiency of hard carbon itself limit its application in lithium-ion batteries. Summary of the invention
[0004] The purpose of the present application is to provide a negative electrode active material, a secondary battery comprising the negative electrode active material, and an electronic device.
[0005] According to the first aspect of the present application, the present application provides a negative electrode active material, which is in a granular form, and the negative electrode active material includes secondary particles formed by a first phase material and a second phase material; the secondary particles are formed by coating the second phase material on the surface of the first phase material, and / or, are formed by agglomerating the first phase material and the second phase material; there are pores inside the secondary particles, and the pores are distributed between the first phase and the second phase of the secondary particles, and the area percentage of the pores in a single secondary particle is 0.5% to 35%.
[0006] The negative electrode active material provided in the present application is in a granular form and is a secondary particle formed by a first phase material and a second phase material. The present application can make the first phase and the second phase have good contact by regulating the special arrangement of the first phase and the second phase in the negative electrode active material, ensure electron transfer, and then reduce the electrode sheet resistance, improve the compaction density of the active material, and then improve the energy density of the secondary battery while improving the cycle performance of the secondary battery; at the same time, the present application has found through research that reserving pores between the first phase material and the second phase material can alleviate the volume expansion of the first phase material during the cycle and improve the cycle stability of the negative electrode active material. And the inventor of the present application further found that in the cross section of a single secondary particle in the negative electrode active material, the percentage of the area occupied by the pores between the first phase material and the second phase material will further affect the stability of the negative electrode active material. The percentage of the area occupied by the pores is regulated within the above range, which can avoid the loss of the electrolyte while giving the first phase material space to expand during the cycle, further alleviating the volume expansion of the first phase material during the cycle, thereby further improving the cycle stability of the negative electrode active material. If the area percentage of the pores in a single secondary particle exceeds the above range, for example, if it is lower than the above range, the reserved pores will be insufficient to meet the expansion of the particles, and the cyclic expansion of the first phase particles will easily lead to the breakage of the secondary particles, thereby reducing the cyclic stability of the secondary battery. If it is higher than the above range, the exposed active area will increase, the first efficiency will decrease, the energy density of the battery cell will be low, and the amount of electrolyte consumed in the cycle will increase, affecting the cyclic performance of the secondary battery.
[0007] In some embodiments of the present application, the area percentage of the pores in a single secondary particle is 18% to 30%. The present application has been found through research that when the area percentage of the pores is further controlled within the above range, the loss of electrolyte can be avoided while giving graphite space to expand during the cycle, further alleviating the volume expansion of the first phase material during the cycle, thereby further improving the cycle stability of the negative electrode active material. If the area percentage of the pores in a single secondary particle exceeds the above range, such as being lower than the above range, the reserved pores will be insufficient to meet the particle expansion, the cyclic expansion of the first phase particles will easily lead to the breakage of the secondary particles, and the cycle stability of the secondary battery will be reduced. If it is higher than the above range, it will lead to an increase in the exposed active area, a decrease in the first effect, a low energy density of the battery cell, and an increase in the amount of electrolyte consumed in the cycle, affecting the cycle performance of the secondary battery.
[0008] In some embodiments of the present application, there are circular holes in the cross section of the second phase material, and the diameter of the circular holes is D1, and D1 satisfies: 45nm≤D1≤550nm. In the negative electrode active material provided in the present application, there are circular holes in the second phase material. The inventors of the present application have found through research that the presence of circular holes in the second phase material can further alleviate the volume expansion of the second phase material during the cycle and improve the cycle stability of the negative electrode active material; and the present application has found through research that the diameter of the circular holes in the second phase material will affect the cycle stability of the negative electrode active material. When the circular holes in the second phase material are too large, the compaction density of the secondary particles will be too low, and when the circular holes are too small, it will not be conducive to alleviating the volume expansion of the second phase material during the cycle. Regulating the diameter of the circular holes in the second phase material within the above range can further improve the cycle stability of the negative electrode active material, thereby improving the cycle stability of the secondary battery.
[0009] In some embodiments of the present application, there are circular holes in the cross section of the second phase material, and the diameter D1 of the circular holes satisfies: 55nm≤D1≤480nm. By adjusting the diameter of the circular holes in the second phase material within the above range, the cycle stability of the negative electrode active material can be further improved, thereby improving the cycle stability of the secondary battery.
[0010] In some embodiments of the present application, the second phase material contains a first element; the first element includes any one of Li, Na, K, Rb, Mg, Ca, and Zn. The heterogeneous elements (non-carbon elements) in the negative electrode active material will affect the performance of the negative electrode active material. The negative electrode active material provided by the present application, the metal ions introduced in situ can induce the storage of active metal ions in the negative electrode active material, further improving the storage capacity of the negative electrode active metal ions, so that the negative electrode active material has a higher gram capacity and reversible capacity, and further improving the energy density and capacity retention rate of the negative electrode active material.
[0011] In some embodiments of the present application, the content of the first element relative to the total mass of the negative electrode active material is 0.01% to 1.2%. By regulating the content of the first element in the second phase material within the above range, the active metal ions can be further induced to be stored in the negative electrode active material, further improving the storage capacity of the active metal ions, and applying the negative electrode active material of the present application to a secondary battery can further improve the gram capacity of the battery negative electrode, thereby further improving the energy density of the secondary battery.
[0012] In some embodiments of the present application, the content of the first element relative to the total mass of the negative electrode active material is 0.02% to 0.95%. By regulating the content of the first element in the second phase material within the above range, it is more conducive to inducing the storage of active metal ions in the negative electrode active material, and further improving the storage capacity of active metal ions.
[0013] In some embodiments of the present application, the negative electrode active material satisfies at least one of the following conditions (1) to (4):
[0014] (1) The secondary particles have a coating layer on their surface, and the thickness of the coating layer on the secondary particles is in the range of 10 to 110 nm; preferably, the thickness of the coating layer on the secondary particles is in the range of 25 to 100 nm;
[0015] (2) The particle size Dv50 of the first phase material is in the range of 1 μm ≤ Dv50 ≤ 10 μm; preferably, the particle size Dv50 of the first phase material is in the range of 2 μm ≤ Dv50 ≤ 5 μm;
[0016] (3) The ID / IG value of the secondary particles is in the range of 0.4 to 1.2;
[0017] (4) The compaction density of the negative electrode active material is in the range of 1.2 to 1.8 g / cc.
[0018] In the negative electrode active material provided in the present application, the secondary particle surface also has a coating layer, and the coating layer thickness is 10 to 110 nm, preferably, the thickness of the secondary particle surface coating layer ranges from 25 to 100 nm. By providing a coating layer on the surface of the secondary particle and regulating the thickness of the coating layer within the above range, it is helpful to reduce the surface defects of the negative electrode active material, while reducing the exposure of the pore structure in the negative electrode active material, which can improve the first coulomb efficiency of the negative electrode active material, so that the negative electrode active material has a high reversible capacity, thereby improving the energy density and cycle stability of the secondary battery.
[0019] In the negative electrode active material provided in the present application, the particle size Dv50 of the first phase material is in the range of 1μm≤Dv50≤10μm. Preferably, the particle size Dv50 of the first phase material is in the range of 2μm≤Dv50≤5μm. By regulating the particle size Dv50 of the first phase material particles in the secondary particles within the above-mentioned range of the present application, the distribution between the first phase material and the second phase material can be made more uniform, and the formed aggregate structure can be more compact, which can further improve the compaction density of the negative electrode active material and the corresponding negative electrode sheet, thereby improving the energy density of the secondary battery. Among them, Dv50 refers to the particle size measured from the small particle size in the volume-based particle size distribution of the material to reach 50% of the volume accumulation.
[0020] In the negative electrode active material provided in the present application, the ID / IG value of the secondary particles is in the range of 0.4 to 1.2. By regulating the ID / IG value of the secondary particles within the above range, the negative electrode active material can have a suitable degree of defects, which can better promote the adsorption and binding of ions, while reducing the irreversible capacity loss caused by a high degree of defects, thereby helping to improve the gram capacity of the negative electrode active material.
[0021] In the negative electrode active material provided in the present application, the compaction density of the negative electrode active material is 1.2 to 1.8 g / cc. By adjusting the compaction density of the negative electrode active material within the above range, the content of the negative electrode active material per unit area can be increased, thereby increasing the energy density of the secondary battery.
[0022] According to the second aspect of the present application, the present application also provides a method for preparing a negative electrode active material, the preparation method comprising: mixing solid particles corresponding to the first phase material, a precursor corresponding to the second phase material, and a pore-forming agent containing metal elements, spray-drying, carbonizing, screening, and washing the mixed system in sequence, and then forming a coating layer on the surface of the negative electrode active material by vapor deposition to obtain the negative electrode active material.
[0023] In some embodiments of the present application, the method for preparing the negative electrode active material further comprises:
[0024] (1) mixing solid particles corresponding to the first phase material, a precursor corresponding to the second phase material, and a pore-forming agent containing a metal element to obtain a mixed system;
[0025] (2) using a spray drying device to spray dry the mixed system in an environment filled with an inert gas;
[0026] (3) carbonizing the spray-dried mixed precursor under an inert atmosphere;
[0027] (4) crushing and screening the carbonized solids, and then acid washing and water washing;
[0028] (5) Vapor deposition is performed under special atmosphere conditions to form a coating layer on the surface of the negative electrode active material to obtain the negative electrode active material.
[0029] After mixing the first-phase solid particles and the second-phase material precursor and the pore-forming agent containing metal elements, spray drying is performed, and the materials can be mixed evenly and dried and granulated to form secondary particles. The first-phase material has a stable structure and will not be affected by sintering and activating agents. It can be used as a skeleton to support secondary particles. The second-phase material can evenly wrap the first-phase material and form pores between the two-phase materials, further alleviating the volume expansion of the first-phase material during the cycle, thereby further improving the cycle stability of the negative electrode active material; the activator can also form more active sites with the second-phase material to improve the reversible capacity of the negative electrode active material. The negative electrode active material prepared by the method provided in the second aspect of the present application has a stable low potential platform, high gram capacity and high reversible capacity. It is used in the negative electrode plate of a secondary battery, which can improve the energy density of the secondary battery and improve the cycle performance of the secondary battery.
[0030] In some embodiments of the present application, the special atmosphere is a mixture of reducing gas and argon; preferably, the reducing gas includes at least one of acetylene or methane; preferably, based on the volume of the mixture, the volume percentage of the reducing gas is 5% to 20%.
[0031] In some embodiments of the present application, the solid particles corresponding to the first phase material include any one of natural graphite and artificial graphite. The above material is selected as the first phase material, has a stable structure, is not affected by sintering and activating agents, can serve as a skeleton to support secondary particles, and helps to improve the compaction density of the material.
[0032] In some embodiments of the present application, the particle size Dv50 of the solid particles corresponding to the first phase material is in the range of 2μm≤Dv50≤5μm. In the preparation method provided in the present application, the particle size of the solid particles corresponding to the first phase material will affect the percentage of the area occupied by the pores in the cross section of a single particle in the secondary particles of the negative electrode active material finally prepared. By adjusting the particle size of the solid particles corresponding to the first phase material within the above range, the percentage of the area occupied by the pores in the cross section of a single particle in the secondary particles of the negative electrode active material can be further adjusted to be within a suitable range, thereby further achieving the effect of improving the cycle stability of the negative electrode active material.
[0033] In some embodiments of the present application, the precursor corresponding to the second phase material includes at least one of phenolic resin, resorcinol-formaldehyde resin, epoxy resin, cellulose or lignin. At least one of the above materials is selected as the second phase material, so that the second phase material can uniformly wrap the first phase material and form pores between the two phase materials. The volume expansion of the first phase material during the cycle is further alleviated, thereby further improving the cycle stability of the negative electrode active material and improving the cycle performance of the secondary battery.
[0034] In some embodiments of the present application, the pore-forming agent containing alkali metal elements includes at least one of LiOH, NaOH, KOH, RbOH, Mg(OH)2, Ca(OH)2, Zn(OH)2, K2CO3, Na2CO3, sodium carboxymethyl cellulose, and sodium lignin sulfonate. Selecting at least one of the above materials as an activator allows the activator to react with the second phase material to form more active sites, thereby improving the reversible capacity of the negative electrode active material.
[0035] In some embodiments of the present application, the spray drying temperature is T1, and the range of T1 is: 130° C. to 230° C. By regulating the spray drying temperature within the range, it is possible to ensure that the second phase material has a good degree of solidification, and further regulate the diameter of the pores and circular holes inside the material, thereby improving the pyrolysis residual carbon rate of the second phase material and the structural strength of the carbonized material.
[0036] In some embodiments of the present application, the carbonization temperature is T2, and the range of T2 is: 600°C to 1000°C. In some embodiments of the present application, the carbonization time is t1, and the range of t1 is: 1h to 4h. The carbonization temperature and carbonization time in the preparation method of the present application will further affect the content of the first element in the secondary particles. By adjusting the carbonization temperature within the above range of the present application, the content of the first element can be within a more suitable range, further achieving the effect of improving the cycle stability, energy density, capacity retention rate and other performance of the negative electrode active material.
[0037] In some embodiments of the present application, the temperature of the vapor deposition is T3, and the range of T3 is: 700°C to 1200°C. In some embodiments of the present application, the time of the vapor deposition is t2, and the range of t2 is: 0.5h to 20h. By optimizing the vapor deposition conditions, the interface of the material can be improved, the thickness of the coating layer can be controlled, the degradation of the electrolyte can be reduced, the generation of irreversible capacity can be avoided, and the energy density of the secondary battery can be increased while improving the cycle performance of the secondary battery.
[0038] According to the third aspect of the present application, the present application provides a secondary battery, including a positive electrode sheet, a negative electrode sheet and an electrolyte, wherein the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector, and the negative electrode active material layer includes the negative electrode active material provided in the first aspect of the present application or the negative electrode active material prepared according to the preparation method provided in the second aspect of the present application. The secondary battery provided in the third aspect of the present application has high energy density and good cycle performance.
[0039] In some embodiments of the present application, in the provided secondary battery, the negative electrode plate uses lithium metal as the counter electrode, and in the capacity-voltage differential curve obtained by testing in the range of 0 to 2.5V vs Li+ / Li, there are at least 4 characteristic peaks in the charging curve; preferably, the characteristic peaks include F1, F2, F3, and F4, wherein F1 is located between 0.06 and 0.08V in the capacity-voltage differential curve, F2 is located between 0.09 and 0.12V in the capacity-voltage differential curve, F3 is located between 0.13 and 0.15V in the capacity-voltage differential curve, and F4 is located between 0.21 and 0.25V in the capacity-voltage differential curve; preferably, the peak intensity corresponding to F1 is C1, the peak intensity corresponding to F2 is C2, the peak intensity corresponding to F3 is C3, and the relationship between C1 and C2 and C3 satisfies: 0.1≤C1 / C2≤1.0, 1≤C2 / C3≤20. Among the above-mentioned characteristic peaks, the positions of the characteristic peaks near 0.1V and 0.14V are close to those of the graphite negative electrode, which is mainly due to the escape of lithium ions between graphite layers. The broad peak near 0.06-0.08V represents the storage of lithium ions in the second phase material. By regulating the values of C1 / C2 and C2 / C3 in the negative electrode active material within the above-mentioned range, the escape amount of lithium ions in the low platform area can be increased, thereby increasing the gram capacity of the negative electrode material, and then increasing the energy density of the secondary battery.
[0040] In some embodiments of the present application, in the secondary battery provided, the negative electrode plate uses lithium metal as the counter electrode, and in the capacity-voltage differential curve obtained by testing in the range of 0 to 2.5V vs Li+ / Li, there are at least three characteristic peaks in the discharge curve; preferably, the characteristic peaks include E1, E2, and E3, wherein E1 is located at 0.05 to 0.07V in the capacity-voltage differential curve, E2 is located between 0.08 and 0.11V in the capacity-voltage differential curve, and E3 is located between 0.16 and 0.20V; preferably, the peak intensity corresponding to E1 is D1, the peak intensity corresponding to E2 is D2, and the relationship between D1 and D2 satisfies 1.3≤D1 / D2≤3.0. The change in the peak intensity of D1 / D2 represents the change in the storage capacity of lithium ions in the second phase. By regulating the value of D1 / D2 in the negative electrode active material within the above range, the amount of lithium ions embedded in the low platform region can be increased, thereby increasing the gram capacity of the negative electrode material, and then increasing the energy density of the secondary battery.
[0041] According to the fourth aspect of the present application, the present application provides an electronic device, the electronic device comprising the secondary battery described in the third aspect of the present application. The electronic device provided in the fourth aspect of the present application has high energy density and good cycle performance, so that the electronic device provided in the fourth aspect of the present application has a long service life. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other embodiments can also be obtained based on these drawings.
[0043] Figure 1 The scanning electron microscope photographs of the negative electrode active materials of Examples 1-5;
[0044] Figure 2 It is a cross-sectional electron microscope photograph of the negative electrode active material of Example 1-5;
[0045] Figure 3 The charge and discharge curve of the negative electrode active material of Comparative Example 1 in the potential range of Li / Li+ from 0V to 2.5V;
[0046] Figure 4 The capacity-voltage differential curve of the negative electrode active material of Comparative Example 2 in the Li / Li+ potential range of 0V to 2.5V;
[0047] Figure 5 The charge and discharge curves of the negative electrode active materials of Examples 1-9 in the Li / Li+ potential range of 0V to 2.5V;
[0048] Figure 6 Capacity-voltage differential curves of the negative electrode active materials of Examples 1-9 in the potential range of Li / Li+ from 0 V to 2.5 V. DETAILED DESCRIPTION
[0049] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field based on the present application belong to the scope of protection of the present application.
[0050] It should be noted that in the specific implementation manner of the present application, the present application is explained by taking a lithium-ion battery as an example of a secondary battery, but the secondary battery of the present application is not limited to a lithium-ion battery.
[0051] Hard carbon materials have attracted great attention due to their high theoretical capacity, low volume expansion, and fast charge and discharge. In hard carbon materials, lithium ions can be embedded and extracted from all angles, with excellent rate performance and cycle characteristics. However, the compaction density and initial coulomb efficiency of hard carbon itself are low, which limits its application in lithium-ion batteries. Based on this, the inventors of this application started from the negative electrode active material itself, and after a lot of research, found that by optimizing the preparation process of hard carbon materials and compounding graphite with hard carbon materials, a high-capacity, high-initial-efficiency and high-density composite material can be prepared, thereby solving the problems of low gram capacity and poor cycle stability of the negative electrode sheet, and then being able to increase the energy density of the secondary battery while improving the cycle performance of the secondary battery.
[0052] According to the first aspect of the present application, the present application provides a negative electrode active material, which is in a granular form, and the negative electrode active material includes secondary particles formed by a first phase material and a second phase material; the secondary particles are formed by coating the second phase material on the surface of the first phase material, and / or, are formed by agglomerating the first phase material and the second phase material; there are pores inside the secondary particles, and the pores are distributed between the first phase and the second phase of the secondary particles, and the area percentage of the pores in a single secondary particle is 0.5% to 35%.
[0053] Specifically, in the provided negative electrode active material, the area percentage of the pores in a single secondary particle may be 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, or a range consisting of any two of the above values. Preferably, the area percentage of the pores in a single secondary particle may be 18% to 30%.
[0054] The negative electrode active material provided in the present application is in a granular form and is a secondary particle formed by a first phase material and a second phase material. The present application can make the first phase and the second phase have good contact by regulating the special arrangement of the first phase and the second phase in the negative electrode active material, ensure electron transfer, and then reduce the electrode sheet resistance, improve the compaction density of the active material, and then improve the energy density of the secondary battery while improving the cycle performance of the secondary battery; at the same time, the present application has found through research that reserving pores between the first phase material and the second phase material can alleviate the volume expansion of the first phase material during the cycle and improve the cycle stability of the negative electrode active material. And the inventor of the present application further found that in the cross section of a single secondary particle in the negative electrode active material, the percentage of the area occupied by the pores between the first phase material and the second phase material will further affect the stability of the negative electrode active material. The percentage of the area occupied by the pores is regulated within the above range, which can avoid the loss of the electrolyte while giving the first phase material space to expand during the cycle, further alleviating the volume expansion of the first phase material during the cycle, thereby further improving the cycle stability of the negative electrode active material. If the area percentage of the pores in a single secondary particle exceeds the above range, for example, if it is lower than the above range, the reserved pores will be insufficient to meet the expansion of the particles, and the cyclic expansion of the first phase particles will easily lead to the breakage of the secondary particles, thereby reducing the cyclic stability of the secondary battery. If it is higher than the above range, the exposed active area will increase, the first efficiency will decrease, the energy density of the battery cell will be low, and the amount of electrolyte consumed in the cycle will increase, affecting the cyclic performance of the secondary battery.
[0055] In some embodiments of the present application, there are circular holes in the cross section of the second phase material, and the diameter of the circular hole is D1, and D1 satisfies: 45nm≤D1≤550nm. Specifically, the diameter D1 of the circular hole can be 45nm, 46nm, 47nm, 48nm, 49nm, 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, 110nm, 120nm, 130nm, 140nm, 150nm, 160nm, 170nm, 180nm, 190nm, 200nm, 210nm, 220nm, 230nm, 240nm, 250nm, 260nm, 270nm, 280nm 500nm, 510nm, 520nm, 530nm, 540nm, 550nm, or a range consisting of any two of the above values. Preferably, the diameter D1 of the circular hole satisfies: 55nm≤D1≤480nm. In the negative electrode active material provided in the present application, there are circular holes in the second phase material. The inventors of the present application have found through research that the presence of circular holes in the second phase material can further alleviate the volume expansion of the second phase material during the cycle, thereby improving the cycle stability of the negative electrode active material. Moreover, the inventors of the present application have found through research that the diameter of the circular holes in the second phase material will affect the cycle stability of the negative electrode active material. When the circular holes in the second phase material are too large, the compaction density of the secondary particles will be too low, while when the circular holes are too small, it will not be conducive to alleviating the volume expansion of the second phase material during the cycle. By regulating the diameter of the circular holes in the second phase material within the above range, the cycle stability of the negative electrode active material can be further improved, thereby improving the cycle stability of the secondary battery.
[0056] In some embodiments of the present application, the second phase material contains a first element; the first element includes any one of Li, Na, K, Rb, Mg, Ca, and Zn. The heterogeneous elements (non-carbon elements) in the negative electrode active material will affect the performance of the negative electrode active material. The negative electrode active material provided by the present application, the metal ions introduced in situ can induce the storage of active metal ions in the negative electrode active material, further improving the storage capacity of the negative electrode active metal ions, so that the negative electrode active material has a higher gram capacity and reversible capacity, and further improving the energy density and capacity retention rate of the negative electrode active material.
[0057] In some embodiments of the present application, the content of the first element relative to the total mass of the negative electrode active material is 0.01% to 1.2%. Specifically, the content of the first element relative to the total mass of the negative electrode active material can be 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.2%, 0.23%, 0.34%, 0.35%, 0.4%, 0.5%, 0.6%, 0.7%, 0.78%, 0.8%, 0.85%, 0.9%, 0.95%, 1.0%, 1.05%, 1.1%, 1.15%, 1.2% or a range consisting of any two of the above values. Preferably, the content of the first element relative to the total mass of the negative electrode active material can be 0.02% to 0.95%. By regulating the content of the first element in the second phase material within the above range, the active metal ions can be further induced to be stored in the negative electrode active material, further improving the storage capacity of the active metal ions, and applying the negative electrode active material of the present application to a secondary battery can further improve the gram capacity of the battery negative electrode, thereby further improving the energy density of the secondary battery.
[0058] In some embodiments of the present application, the negative electrode active material satisfies at least one of the following conditions (1) to (4):
[0059] (1) The secondary particles have a coating layer on their surface, and the thickness of the coating layer on the secondary particles is in the range of 10 to 110 nm; preferably, the thickness of the coating layer on the secondary particles is in the range of 25 to 100 nm;
[0060] (2) The particle size Dv50 of the first phase material is in the range of 1 μm ≤ Dv50 ≤ 10 μm; preferably, the particle size Dv50 of the first phase material is in the range of 2 μm ≤ Dv50 ≤ 5 μm;
[0061] (3) The ID / IG value of the secondary particles is in the range of 0.4 to 1.2;
[0062] (4) The compaction density of the negative electrode active material is in the range of 1.2 to 1.8 g / cc.
[0063] In some embodiments of the present application, the secondary particle surface has a coating layer, and the thickness of the secondary particle surface coating layer ranges from 10 to 110 nm. Specifically, the thickness of the secondary particle surface coating layer can be 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, 55 nm, 60 nm, 65 nm, 70 nm, 75 nm, 80 nm, 85 nm, 90 nm, 95 nm, 100 nm, 105 nm, 110 nm or a range consisting of any two of the above values. Preferably, the thickness of the secondary particle surface coating layer ranges from 25 to 100 nm. By providing a coating layer on the surface of the secondary particle and regulating the thickness of the coating layer within the above range, it is helpful to reduce the surface defects of the negative electrode active material and reduce the exposure of the pore structure in the negative electrode active material, which can improve the first coulomb efficiency of the negative electrode active material, so that the negative electrode active material has a high reversible capacity, thereby improving the energy density and cycle stability of the secondary battery.
[0064] In some embodiments of the present application, in the negative electrode active material provided, the particle size Dv50 of the first phase material is in the range of 1 μm ≤ Dv50 ≤ 10 μm. Specifically, the particle size Dv50 of the first phase material can be 1 μm, 1.5 μm, 2 μm, 2.1 μm, 2.2 μm, 2.3 μm, 2.4 μm, 2.5 μm, 2.6 μm, 2.7 μm, 2.8 μm, 2.9 μm, 3.0 μm, 3.1 μm, 3.2 μm, 3.3 μm, 3.4 μm, 3.5 μm, 3.6 μm, 3.7 μm, 3.8 μm, 3.9μm, 4.0μm, 4.1μm, 4.2μm, 4.3μm, 4.4μm, 4.5μm, 4.6μm, 4.7μm, 4.8μm, 4.9μm, 5μm, 5.5μm, 6.0μm, 6.5μm, 7.0μm, 7.5μm, 8.0μm, 8.5μm, 9.0μm, 9.5μm, 10μm or a range consisting of any two of the above values. Preferably, the particle size Dv50 of the first phase material is in the range of 2μm≤Dv50≤5μm. By regulating the particle size Dv50 of the first phase material particles in the secondary particles within the above range of the present application, the first phase material and the second phase material can be more evenly distributed, the formed aggregate structure can be more compact, and the compaction density of the negative electrode active material and the corresponding negative electrode sheet can be further improved, thereby improving the energy density of the secondary battery. Here, Dv50 refers to the particle size at which the volume accumulation reaches 50% in the volume-based particle size distribution of the material, measured from the smallest particle size.
[0065] In some embodiments of the present application, the ID / IG value of the secondary particles is in the range of 0.4 to 1.2. Specifically, the ID / IG value of the secondary particles can be 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2 or a range consisting of any two of the above values. By regulating the range of the ID / IG value of the secondary particles within the above range, the negative electrode active material can have a suitable degree of defects, which can better promote the adsorption and binding of ions, while reducing the irreversible capacity loss caused by a high degree of defects, thereby helping to improve the gram capacity of the negative electrode active material.
[0066] In some embodiments of the present application, the compaction density of the negative electrode active material is in the range of 1.2 to 1.8 g / cc. Specifically, the compaction density of the negative electrode active material can be 1.2 g / cc, 1.3 g / cc, 1.4 g / cc, 1.5 g / cc, 1.6 g / cc, 1.7 g / cc, 1.8 g / cc, or a range consisting of any two of the above values. By regulating the compaction density of the negative electrode active material within the above range, the content of the negative electrode active material per unit area can be increased, thereby increasing the energy density of the secondary battery.
[0067] According to the second aspect of the present application, the present application also provides a method for preparing a negative electrode active material, the preparation method comprising: mixing solid particles corresponding to the first phase material, a precursor corresponding to the second phase material, and a pore-forming agent containing metal elements, spray-drying, carbonizing, screening, and washing the mixed system in sequence, and then forming a coating layer on the surface of the negative electrode active material by vapor deposition to obtain the negative electrode active material.
[0068] In some embodiments of the present application, the method for preparing the negative electrode active material further comprises:
[0069] (1) mixing solid particles corresponding to the first phase material (precursor 1), a precursor corresponding to the second phase material (precursor 2), and a pore-forming agent containing a metal element to obtain a mixed system;
[0070] (2) using a spray drying device to spray dry the mixed system in an environment filled with an inert gas;
[0071] (3) carbonizing the spray-dried mixed precursor under an inert atmosphere;
[0072] (4) crushing and screening the carbonized solids, and then acid washing and water washing;
[0073] (5) Vapor deposition is performed under special atmosphere conditions to form a coating layer on the surface of the negative electrode active material to obtain the negative electrode active material.
[0074] After mixing the first-phase solid particles, the second-phase material precursor, and the pore-forming agent containing metal elements, spray drying is performed, and the materials can be mixed evenly and dried and granulated to form secondary particles. The first-phase material has a stable structure and will not be affected by sintering and activating agents. It can be used as a skeleton to support secondary particles. The second-phase material can evenly wrap the first-phase material and form pores between the two-phase materials, further alleviating the volume expansion of the first-phase material during the cycle, thereby further improving the cycle stability of the negative electrode active material. The activator and the second-phase material can also form more active sites and improve the reversible capacity of the negative electrode active material. Controlling the carbonization conditions of the particles can adjust the degree of reaction between the activator and the second-phase material, control the internal pores and the first element content, and obtain better lithium storage performance. Optimizing the vapor deposition conditions can improve the interface of the material, control the thickness of the coating layer, reduce the degradation of the electrolyte, avoid the generation of irreversible capacity, increase the energy density of the secondary battery, and improve the cycle performance of the secondary battery. The negative electrode active material prepared by the method provided in the second aspect of the present application has a stable low potential platform, high gram capacity and high reversible capacity. Using it as the negative electrode plate of a secondary battery can increase the energy density of the secondary battery and improve the cycle performance of the secondary battery.
[0075] In some embodiments of the present application, the special atmosphere is a mixture of reducing gas and argon; preferably, the reducing gas includes at least one of acetylene or methane; preferably, based on the volume of the mixed gas, the volume percentage of the reducing gas is 5% to 20%. Specifically, based on the volume of the mixed gas, the volume percentage of the reducing gas can be 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, or a range consisting of any two of the above values.
[0076] In some embodiments of the present application, the solid particles corresponding to the first phase material include any one of natural graphite and artificial graphite. The above material is selected as the first phase material, has a stable structure, is not affected by sintering and activating agents, can serve as a skeleton to support secondary particles, and helps to improve the compaction density of the material.
[0077] In some embodiments of the present application, the particle size Dv50 of the solid particles corresponding to the first phase material is in the range of 1 μm ≤ Dv50 ≤ 10 μm. Specifically, the particle size Dv50 of the solid particles corresponding to the first phase material can be 1 μm, 1.5 μm, 2 μm, 2.1 μm, 2.2 μm, 2.3 μm, 2.4 μm, 2.5 μm, 2.6 μm, 2.7 μm, 2.8 μm, 2.9 μm, 3.0 μm, 3.1 μm, 3.2 μm, 3.3 μm, 3.4 μm, 3.5 μm, 3.6 μm, 3.7 μm, 3.8 10μm, or a range consisting of any two of the above values. Preferably, the particle size Dv50 of the solid particles corresponding to the first phase material is in the range of 2μm≤Dv50≤5μm. In the preparation method provided in the present application, the particle size of the solid particles corresponding to the first phase material will affect the percentage of the area occupied by the pores in the cross section of a single particle in the secondary particles of the negative electrode active material finally prepared. By controlling the particle size of the solid particles corresponding to the first phase material within the above-mentioned range, the percentage of the area occupied by the pores in the cross section of a single particle in the secondary particles of the negative electrode active material can be further controlled within an appropriate range, thereby further achieving the effect of improving the cycle stability of the negative electrode active material.
[0078] In some embodiments of the present application, the precursor corresponding to the second phase material includes at least one of phenolic resin, resorcinol-formaldehyde resin, epoxy resin, cellulose or lignin. At least one of the above materials is selected as the second phase material, so that the second phase material can uniformly wrap the first phase material and form pores between the two phase materials. The volume expansion of the first phase material during the cycle is further alleviated, thereby further improving the cycle stability of the negative electrode active material and improving the cycle performance of the secondary battery.
[0079] In some embodiments of the present application, the pore-forming agent containing alkali metal elements includes at least one of LiOH, NaOH, KOH, RbOH, Mg(OH)2, Ca(OH)2, Zn(OH)2, K2CO3, Na2CO3, sodium carboxymethyl cellulose, and sodium lignin sulfonate. Selecting at least one of the above materials as an activator allows the activator to react with the second phase material to form more active sites, thereby improving the reversible capacity of the negative electrode active material.
[0080] In some embodiments of the present application, the spray drying temperature is T1, and the range of T1 is: 130°C to 230°C. Specifically, the spray drying temperature T1 can be: 130°C, 135°C, 140°C, 145°C, 150°C, 155°C, 160°C, 165°C, 170°C, 175°C, 180°C, 185°C, 190°C, 195°C, 200°C, 205°C, 210°C, 215°C, 220°C, 225°C, 230°C or a range consisting of any two of the above values. By regulating the spray drying temperature within the range, it can be ensured that the second phase material has a good degree of solidification, and the diameter of the internal pores and circular holes of the material can be further regulated to improve the pyrolysis residual carbon rate of the second phase material and the structural strength of the carbonized material.
[0081] In some embodiments of the present application, the carbonization temperature is T2, and the range of T2 is: 600°C to 1000°C. Specifically, the carbonization temperature T2 can be 600°C, 650°C, 700°C, 710°C, 720°C, 730°C, 740°C, 750°C, 760°C, 770°C, 780°C, 790°C, 800°C, 810°C, 820°C, 830°C, 840°C, 850°C, 860°C, 870°C, 880°C, 890°C, 900°C, 950°C, 1000°C or a range consisting of any two of the above values.
[0082] In some embodiments of the present application, the carbonization time is t1, and the range of t1 is: 1h to 4h. Specifically, the carbonization time t1 can be 1h, 1.1h, 1.2h, 1.3h, 1.4h, 1.5h, 1.6h, 1.7h, 1.8h, 1.9h, 2.0h, 2.1h, 2.2h, 2.3h, 2.4h, 2.5hh, 2.6h, 2.7h, 2.8h, 2.9h, 3.0h, 3.1h, 3.2h, 3.3h, 3.4h, 3.5h, 3.6h, 3.7h, 3.8h, 3.9h, 4.0h or a range consisting of any two of the above values.
[0083] The carbonization temperature and carbonization time in the preparation method of the present application will further affect the content of the first element in the secondary particles. By adjusting the carbonization temperature within the above-mentioned range of the present application, the content of the first element can be within a more appropriate range, thereby further achieving the effect of improving the cycle stability, energy density, capacity retention rate and other performance of the negative electrode active material.
[0084] In some embodiments of the present application, the temperature of the vapor deposition is T3, and the range of T3 is: 700°C to 1200°C. Specifically, the temperature T3 of the vapor deposition can be 700°C, 750°C, 800, 850°C, 900°C, 950°C, 1000°C, 1050°C, 1100°C, 1150°C, 1200°C, or a range consisting of any two of the above values. In some embodiments of the present application, the time of the vapor deposition is t2, and the range of t2 is: 0.5h to 20h. Specifically, the time t2 of the vapor deposition can be 0.5h, 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h, or a range consisting of any two of the above values. By optimizing the vapor deposition conditions, the interface of the material can be improved, the thickness of the coating layer can be controlled, the degradation of the electrolyte can be reduced, the generation of irreversible capacity can be avoided, and the energy density of the secondary battery can be increased while improving the cycle performance of the secondary battery.
[0085] According to the third aspect of the present application, the present application provides a secondary battery, including a positive electrode sheet, a negative electrode sheet and an electrolyte, wherein the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector, and the negative electrode active material layer includes the negative electrode active material provided in the first aspect of the present application or the negative electrode active material prepared according to the preparation method provided in the second aspect of the present application. The secondary battery provided in the third aspect of the present application has high energy density and good cycle performance.
[0086] In some embodiments of the present application, in the provided secondary battery, the negative electrode plate uses lithium metal as the counter electrode, and in the capacity-voltage differential curve obtained by testing in the range of 0 to 2.5V vs Li+ / Li, there are at least 4 characteristic peaks in the charging curve; preferably, the characteristic peaks include F1, F2, F3, and F4, wherein F1 is located between 0.06 and 0.08V in the capacity-voltage differential curve, F2 is located between 0.09 and 0.12V in the capacity-voltage differential curve, F3 is located between 0.13 and 0.15V in the capacity-voltage differential curve, and F4 is located between 0.21 and 0.25V in the capacity-voltage differential curve; preferably, the peak intensity corresponding to F1 is C1, the peak intensity corresponding to F2 is C2, and the peak intensity corresponding to F3 is C3, and the relationship between C1 and C2 and C3 satisfies: 0.1≤C1 / C2≤1.0, 1≤C2 / C3≤20. Specifically, C1 / C2 can be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0 or a range consisting of any two of the above values. Specifically, C2 / C3 can be 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20 or a range consisting of any two of the above values. Among the above characteristic peaks, the position of the characteristic peaks near 0.1V and 0.14V is close to that of the graphite negative electrode, which is mainly caused by the release of lithium ions between graphite layers. The broad peaks near 0.06 to 0.08V represent the storage of lithium ions in the second phase material. By regulating the values of C1 / C2 and C2 / C3 in the negative electrode active material within the above range, the release amount of lithium ions in the low platform area can be increased, thereby increasing the gram capacity of the negative electrode material, and then increasing the energy density of the secondary battery.
[0087] In some embodiments of the present application, in the provided secondary battery, the negative electrode plate uses lithium metal as the counter electrode, and in the capacity-voltage differential curve obtained by testing in the range of 0 to 2.5V vs Li+ / Li, there are at least three characteristic peaks in the discharge curve; preferably, the characteristic peaks include E1, E2, and E3, wherein E1 is located at 0.05 to 0.07V in the capacity-voltage differential curve), E2 is located at 0.05 to 0.07V in the capacity-voltage differential curve, and E3 is located between 0.16 and 0.20V; preferably, the peak intensity corresponding to E1 is D1, the peak intensity corresponding to E2 is D2, and the relationship between D1 and D2 satisfies 1.3≤D1 / D2≤3.0. Specifically, D1 / D2 can be 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0 or a range consisting of any two of the above values. The change in the peak intensity of D1 / D2 represents the change in the storage capacity of lithium ions in the second phase. By regulating the value of D1 / D2 in the negative electrode active material within the above range, the amount of lithium ions embedded in the low platform area can be increased, thereby increasing the gram capacity of the negative electrode material, and then increasing the energy density of the secondary battery.
[0088] The present application has no particular restrictions on the negative electrode current collector, as long as the purpose of the present application can be achieved. For example, the negative electrode current collector may include copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, foamed nickel, foamed copper, or a polymer substrate coated with a conductive metal.
[0089] The negative electrode active material layer of the present application may also include a conductive agent and a binder. The present application has no particular restrictions on the above conductive agent and the above binder, as long as the purpose of the present application can be achieved. For example, the conductive agent may include but is not limited to carbon materials, metals or conductive polymers. The binder may include but is not limited to at least one of polypropylene alcohol, sodium polyacrylate, potassium polyacrylate, lithium polyacrylate, polyimide, polyamide-imide, hydroxypropyl cellulose, carboxymethyl cellulose (CMC) or sodium carboxymethyl cellulose (CMC-Na).
[0090] The secondary battery of the present application also includes a positive electrode sheet. The present application has no particular restrictions on the positive electrode sheet, as long as the purpose of the present application can be achieved. For example, the positive electrode sheet includes a positive current collector and a positive active material layer arranged on at least one surface of the positive current collector. For example, the positive current collector may include a metal foil or a composite current collector, etc. For example, the metal foil is aluminum foil. In some embodiments, the secondary battery is a lithium-ion battery, and the positive electrode active material may include a lithium transition metal oxide, and the lithium transition metal oxide may include but is not limited to at least one of lithium iron phosphate, lithium-rich manganese-based materials, lithium cobalt oxide (LiCoO2), lithium iron manganese phosphate or lithium titanate.
[0091] The present application has no particular limitation on the thickness of the positive electrode current collector and the positive electrode active material layer, as long as the purpose of the present application can be achieved. For example, the thickness of the positive electrode current collector is 5 μm to 20 μm, preferably 6 μm to 18 μm.
[0092] The secondary battery of the present application also includes an electrolyte. In one embodiment, the electrolyte includes a lithium salt and a non-aqueous solvent. The present application has no particular limitation on the concentration of the lithium salt in the electrolyte, as long as the purpose of the present application can be achieved.
[0093] The secondary battery of the present application also includes a diaphragm to separate the positive electrode plate and the negative electrode plate, prevent the internal short circuit of the secondary battery, allow the electrolyte ions to pass freely, and do not affect the electrochemical charge and discharge process. The present application has no special restrictions on the diaphragm, as long as the purpose of the present application can be achieved. For example, the material of the diaphragm can include but is not limited to polyethylene (PE), polypropylene (PP), polytetrafluoroethylene-based polyolefin (PO) diaphragms, polyester films (such as polyethylene terephthalate (PET) films), cellulose films, polyimide films (PI), polyamide films (PA), spandex or aramid films, etc. At least one of the above.
[0094] The secondary battery of the present application also includes a packaging bag for containing a positive electrode sheet, a separator, a negative electrode sheet and an electrolyte, as well as other components known in the art in the secondary battery, and the present application does not limit the above-mentioned other components. The present application does not specifically limit the packaging bag, and it can be a packaging bag known in the art, as long as it can achieve the purpose of the present application. For example, an aluminum-plastic film packaging bag can be used.
[0095] The secondary battery of the present application is not particularly limited, and may include any device that undergoes an electrochemical reaction. In one embodiment of the present application, the secondary battery may include, but is not limited to, a lithium ion battery, a sodium ion battery, a lithium polymer secondary battery, or a lithium ion polymer secondary battery.
[0096] According to the fourth aspect of the present application, the present application provides an electronic device, the electronic device comprising the secondary battery described in the third aspect of the present application. The secondary battery provided in the third aspect of the present application has high energy density and good cycle performance, so that the electronic device provided in the fourth aspect of the present application has a long service life.
[0097] The electronic device of the present application is not particularly limited, and it can be any electronic device known in the prior art. In some embodiments, the electronic device can include but is not limited to a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD TV, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery or a lithium-ion capacitor, etc.
[0098] Example
[0099] The following examples and comparative examples are given to more specifically describe the embodiments of the present application. Various tests and evaluations were performed according to the following methods. In addition, unless otherwise specified, "parts" and "%" are based on mass.
[0100] The test methods and equipment used in the examples and comparative examples of the present application are as follows:
[0101] 1. Scanning electron microscope (SEM) test
[0102] The prepared negative electrode active material particles were observed using a scanning electron microscope (instrument model: ZEISSSEM), and SEM photos were taken. The pores and circular holes of the particles were measured using the measurement function of the scanning electron microscope.
[0103] For cross-section testing, an ion polisher (instrument model: IB-09010CP) was used to cut out a flat cross section, followed by SEM photography. The principle of ion polishing is that under vacuum conditions, an ion source ionizes argon gas. After acceleration and focusing, high-speed argon ions knock out atoms or molecules on the sample surface to achieve ion polishing.
[0104] For the negative electrode active material particles, the calculation / statistical method for the percentage of the area occupied by pores in a single particle is: using the measurement function of a scanning electron microscope, the cross-sectional area S1 of a single particle is measured and calculated, and at the same time, the pore area S2 in the cross-section of a single particle is measured and calculated. The percentage of the area of pores in a single particle is S2 / S1×100%.
[0105] For the negative electrode active material particles, the diameter of the circular pores in the particles is calculated / statisticed in the following way: using the measurement function of a scanning electron microscope to measure and calculate the diameter of the circular pores in the particles.
[0106] 2. Transmission electron microscopy (TEM) test
[0107] A transmission electron microscope (FEI Tecnai F20) was used to observe the carbon coating layer of the prepared negative electrode active material, and TEM photos were taken to measure the thickness of the carbon coating layer of the negative electrode active material.
[0108] 3. Particle size test
[0109] The particle size distribution of the prepared negative electrode active material was tested using a Malvern particle size tester (instrument model: Master Sizer 2000). In the volume-based particle size distribution of the material, starting from the small particle size, the particle size reaching 50% of the volume accumulation is Dv50, and the particle size reaching 99% of the volume accumulation is Dv99.
[0110] 4. Metal element analysis test
[0111] The sample was digested by a microwave digestion instrument (model CEM-Mars5), and the element content in the prepared negative electrode active material was quantitatively tested using an ICP-OES instrument (instrument model PE7000DV). After the sample was digested into a solution by acid, the liquid sample entered the atomization chamber, and formed an aerosol under the action of the carrier gas, and entered the plasma through the central injection tube to be fully evaporated, dissociated, atomized, ionized and excited, emitting the characteristic spectral line of the element, which was qualitatively analyzed according to the wavelength of the spectral line, and quantitatively analyzed according to the proportionality of the spectral line intensity to the concentration.
[0112] 5. Raman test
[0113] The Raman spectrum of the prepared negative electrode active material was tested by Raman spectrometer. The range of 200μm×500μm was selected for testing, and more than 200 points were tested at equal intervals within the range. The test range of each point was 1000cm -1 Up to 2000cm -1 Between; 1320cm -1 Up to 1370cm -1 The peak between the two is recorded as D peak, at 1570 cm -1 Up to 1620cm -1 The peak between the two points is the G peak, and the I D / I G The intensity ratio of the points is then calculated as the average value of the multiple points. D / I G Strength ratio.
[0114] 6. Powder compaction density test of negative electrode active material:
[0115] With reference to the standard GB / T 24533-2009, the test was carried out using the Sansi Zongheng UTM7305 electronic pressure testing machine. A certain mass of negative electrode active material powder was weighed and added to a special compaction mold. The mold was hollow in the middle with a metal disc on the top and bottom. The powder was placed between the metal discs and a metal cylinder was placed on the top. The mold was placed on a compaction density instrument and the required test tonnage was set to 5 tons. The thickness of the powder under the corresponding pressure can be read on the equipment. The corresponding compaction density of the negative electrode active material can be calculated using the density formula.
[0116] 7. Total gram capacity of lithium storage of negative electrode active materials and first efficiency test:
[0117] The first reversible gram capacity of the negative electrode active material at 0V to 2.5V can be obtained by the following test method: take a single-sided coated negative electrode sheet, cut it into a disc with a diameter of 14mm and use it as a working electrode, then use a lithium sheet as a counter electrode, and a polyethylene film with a porosity of 35% as a separator, inject an electrolyte and assemble to obtain a button battery, wherein the electrolyte includes a basic solvent and a lithium salt, the basic solvent is obtained by mixing ethylene carbonate (EC) and diethyl carbonate (DEC) in a mass ratio of 1:1, the lithium salt is LiPF6, and the lithium salt concentration is 2.5-3.5. is 1mol / L; the button battery is first discharged to 0V with a three-stage small current of 0.05C / 0.01C / 0.005C, and the first discharge capacity of the button battery is recorded; then it is charged to 2.5V with a constant current of 0.1C, and the first charging capacity of the button battery is recorded; the first efficiency = first charging capacity / first discharge capacity × 100%; the first reversible gram capacity of the negative electrode active material from 0V to 2.5V, that is, the total gram capacity of lithium storage (total reversible capacity) = first charging capacity / mass of the negative electrode active material, the unit is mAh / g.
[0118] 8. Capacity-voltage differential curve test of negative electrode active materials
[0119] The same as the first reversible gram capacity test method of the negative electrode active material at 0V to 2.5V, the capacity-voltage curve is converted into a capacity-voltage differential curve, namely, a dQ / dV curve, using corresponding software.
[0120] 9. Energy density (ED) test
[0121] In an environment of 25°C, the lithium-ion battery is charged at a constant current of 0.2C to a voltage of 4.48V or 3.95V, and then charged at a constant voltage; discharged at a constant current of 0.2C to a voltage of 2V, which is recorded as one cycle, and the discharge capacity C and discharge energy E of the first cycle are recorded; and the length, width and height of the battery at a 50% charge state are tested to obtain the volume V of the battery m Average discharge voltage U = E / C; energy density ED = E / V m .
[0122] Example 1-1
[0123] <Preparation of negative electrode active material>
[0124] 80g of natural graphite (precursor 1) was weighed and dispersed in 1L of water, wherein the particle size Dv50 of the natural graphite was 2μm, and then 40g of lignin (precursor 2) and 5g of pore-forming agent NaOH were added, and the dispersion was stirred at room temperature for 3h until the sample was completely dispersed; then the temperature was increased to 60°C at a heating rate of 5°C / min, reacted for 6h, cooled, and a pre-reacted dispersion was obtained after cooling; the prepared dispersion was dried by spray drying, and the air inlet temperature was controlled to be T1=200°C. After the spraying was completed, the powder product was collected; the powder product was placed in a rotary kiln containing an inner tank as a mixed precursor, and the temperature was increased to a primary calcination temperature T at a heating rate of 5°C / min. 2=700℃, carbonization time t1=2h, cool down, and obtain the carbonized material after cooling. Then wash the collected powder with 1M hydrochloric acid for 12h, take the filter residue after suction filtration, wash it with deionized water for 12h, filter and dry the filter residue; then transfer the dried powder into a nitrogen atmosphere protection furnace, and heat it to the vapor deposition temperature T3=800℃ at a heating rate of 5℃ / min, and then replace the gas atmosphere with a mixture of reducing gas acetylene and argon (based on the mass of the mixed gas, the mass percentage of reducing gas acetylene is 20%), vapor deposition time t2=4h, disconnect the above-mentioned mixed gas after the vapor deposition, replace it with nitrogen, and wait for cooling to room temperature to obtain a hard carbon material, i.e., a negative electrode active material.
[0125] <Preparation of negative electrode sheet>
[0126] The negative electrode active material, binder styrene butadiene rubber, and thickener sodium carboxymethyl cellulose prepared above were mixed in a mass ratio of 97:1.5:1.5, and then deionized water was added as a solvent to prepare a negative electrode slurry with a solid content of 40wt%, and stirred evenly. The negative electrode slurry was evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 6μm, and the copper foil was dried at 85°C for 4h to obtain a negative electrode sheet with a single-sided coating of a negative electrode active material layer with a coating thickness of 50μm. After cold pressing, cutting, and slitting, it was dried under vacuum conditions at 120°C for 12h to obtain a negative electrode sheet with a specification of 76.6mm×875mm.
[0127] <Preparation of positive electrode sheet>
[0128] The positive electrode active material lithium cobalt oxide, the conductive agent conductive carbon black (Super P), and the binder PVDF are mixed in a mass ratio of 97:1.4:1.6, and N-methylpyrrolidone (NMP) is added as a solvent, stirred evenly, and a positive electrode slurry with a solid content of 72wt% is prepared. The positive electrode slurry is evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 13μm, and dried at 85°C to obtain a positive electrode sheet with a single-sided coating of positive electrode active material and a positive electrode active material layer thickness of 80μm. After cold pressing, cutting, and slitting, it is dried under vacuum conditions at 85°C for 4h to obtain a positive electrode sheet with a specification of 74mm×867mm.
[0129] <Preparation of Electrolyte>
[0130] In a dry argon atmosphere glove box, the base solvents ethylene carbonate (EC), propylene carbonate (PC), and diethyl carbonate (DEC) were mixed in a mass ratio of EC:PC:DEC=1:1:1, and then 1,3-propane sultone, fluoroethylene carbonate, and succinonitrile were added, dissolved and fully stirred, and then lithium salt LiPF6 was added and mixed evenly to obtain an electrolyte, wherein the concentration of the lithium salt was 1 mol / L, and based on the mass of the base solvent, the mass percentages of 1,3-propane sultone, fluoroethylene carbonate, and succinonitrile were all 2%.
[0131] <Preparation of Separator>
[0132] A polyethylene film with a thickness of 7 μm was used as the separator.
[0133] <Preparation of lithium-ion batteries>
[0134] The prepared positive electrode sheet, separator, and negative electrode sheet are stacked in order, so that the separator is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then wound to obtain an electrode assembly. After welding the pole ear, the electrode assembly is placed in an aluminum-plastic film packaging bag, placed in a vacuum oven at 80°C for 12 hours to remove moisture, and the prepared electrolyte is injected. After vacuum packaging, standing, formation, degassing, shaping and other processes, a lithium-ion battery is obtained.
[0135] Example 1-2 to Example 1-24
[0136] Except for adjusting the preparation parameters according to Table a, the remaining parameters of Examples 1-2 to 1-24 are the same as those of Example 1-1.
[0137] Table a
[0138]
[0139]
[0140] Examples 1-25
[0141] Based on Example 1-5, the step of adding the pore-forming agent NaOH was removed to prepare the negative electrode active material. The remaining steps and parameters were the same as those of Example 1-5. The relevant parameters and relevant properties of the prepared negative electrode active materials were compared.
[0142] Examples 1-26
[0143] Based on Examples 1-5, the step of adding natural graphite was removed to prepare the negative electrode active material. The remaining steps and parameters were the same as those of Examples 1-5. The relevant parameters and relevant properties of the prepared negative electrode active materials were compared.
[0144] Comparative Example 1
[0145] Coconut shell is used to replace the mixed precursor used in <Preparation of negative electrode active material> in Example 1-1, that is, coconut shell is used as a precursor, the precursor is directly placed in a rotary kiln containing an inner shell, and the temperature is increased to a primary calcination temperature T2 = 700 ° C at a heating rate of 5 ° C / min, the carbonization time t1 = 2h, and the temperature is reduced to obtain the carbonized material after cooling. The remaining subsequent steps are the same as in Example 1.
[0146] Comparative Example 2
[0147] The commercially purchased artificial graphite was heated to 700°C in a rotary furnace under 10% C2H2 gas and maintained for 2 hours, and then the gas was switched to N2 gas and the final graphite material was obtained after natural cooling.
[0148] Comparative Example 3
[0149] Based on Examples 1-5, the step of adding lignin was removed to prepare the negative electrode active material. The remaining steps and parameters were the same as those of Examples 1-5. The relevant parameters and relevant properties of the prepared negative electrode active materials were compared.
[0150] The relevant parameters and relevant properties of the active materials prepared in the above embodiments and comparative examples were tested by the above test methods, and the results are shown in Table 1:
[0151] Table 1
[0152]
[0153]
[0154] The results shown in Table 1 show that the negative electrode active material provided by the present application has a higher energy density and a significantly improved cycle performance. Figure 1 The scanning electron microscope photographs of the negative electrode active materials of Examples 1-5 of the present application are shown. Figure 1It can be seen that the negative electrode active material provided in the present application is in a granular form, and the particles are secondary particles formed by aggregation of primary particles. Figure 2 The cross-sectional electron micrographs of the negative electrode active materials of Examples 1-5 of the present application are shown, combined with Figure 2 It can be seen that the secondary particles in the negative electrode active material provided in the present application include a first phase material and a second phase material, and the secondary particles are formed by coating the second phase material on the surface of the first phase material, and / or by aggregating the first phase material and the second phase material, and according to Figure 2 The cross-sectional electron microscope photo shown shows that there are pores inside the secondary particles of the negative electrode active material provided in the present application, and the pores are distributed between the first phase and the second phase of the secondary particles. And according to the data of the embodiments and comparative examples presented in Table 1, it is further shown that by controlling the area percentage of the pores in a single secondary particle within the scope of the present application, the energy density of the negative electrode active material can be significantly improved while the cycle performance can be significantly improved.
[0155] at the same time, Figure 3 The charge and discharge curves of a battery assembled with a negative electrode sheet prepared from the negative electrode active material prepared in Comparative Example 1 as the working electrode and a lithium metal sheet as the counter electrode in the Li / Li+ potential range of 0V to 2.5V are shown. Figure 3 It can be seen that in the Li / Li+ potential range of 0V to 0.2V, the specific capacity of the negative electrode active material of Comparative Example 1 is 233mAh / g; in the Li / Li+ potential range of 0V to 2.5V, the specific capacity of the negative electrode active material of Comparative Example 1 is 454mAh / g.
[0156] Figure 4 The figure shows a battery assembled with a negative electrode sheet prepared from the negative electrode active material prepared in Comparative Example 2 as a working electrode and a lithium metal sheet as a counter electrode, and a capacity-voltage differential curve in the Li / Li+ potential range of 0V to 2.5V. It can be seen from the capacity-voltage differential curve that there are three obvious characteristic peaks in the charging curve, among which the intensities of the characteristic peaks near 0.1V and 0.14V are respectively recorded as C2 and C3, and the peak intensity ratio is C2 / C3=20.8; at the same time, it can also be seen from the capacity-voltage differential curve that there are three obvious characteristic peaks in the discharge curve, among which the intensities of the characteristic peaks near 0.06V and 0.09V are respectively recorded as D1 and D2, and the peak intensity ratio is D1 / D2=1.3.
[0157] Figure 5 The charge and discharge curves of a battery assembled with a negative electrode sheet prepared from the negative electrode active material prepared in Examples 1-9 as a working electrode and a lithium metal sheet as a counter electrode in the Li / Li+ potential range of 0V to 2.5V are shown. Figure 5It can be seen that within the Li / Li+ potential range of 0V to 0.2V, the specific capacity of the negative electrode active material of Examples 1-9 is 323mAh / g; within the Li / Li+ potential range of 0V to 2.5V, the specific capacity of the negative electrode active material of Examples 1-9 is 408mAh / g.
[0158] Figure 6 The capacity-voltage differential curve of a battery assembled with a negative electrode sheet prepared from the negative electrode active material prepared in Examples 1-9 as a working electrode and a lithium metal sheet as a counter electrode in the potential range of Li / Li+ from 0V to 2.5V is shown. It can be seen from the capacity-voltage differential curve that there are 4 obvious characteristic peaks in the charging curve, among which there is a broad peak near 0.06-0.08V, and the peak intensity is recorded as C1, and the intensities of the characteristic peaks near 0.1V and 0.14V are recorded as C2 and C3, respectively, and the peak intensity ratio satisfies C1 / C2=0.19 and C2 / C3=1.7; at the same time, it can also be seen from the capacity-voltage differential curve that there are 3 obvious characteristic peaks in the discharge curve, among which the intensities of the characteristic peaks near 0.06V and 0.09V are recorded as D1 and D2, respectively, and the peak intensity ratio is D1 / D2=2.0.
[0159] It is to be understood that the present invention is described by some embodiments, and it is known to those skilled in the art that various changes or equivalent substitutions may be made to these features and embodiments without departing from the scope of the present invention. In addition, under the teachings of the present invention, these features and embodiments may be modified to adapt to specific circumstances and materials without departing from the scope of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed herein, and all embodiments falling within the scope of the claims of the present invention are within the scope of protection of the present invention.
Claims
1. A negative electrode active material, characterized in that: The negative electrode active material is in a particle shape, and includes secondary particles formed by a first phase material and a second phase material; pores exist inside the secondary particles, and the area percentage of the pores in a single secondary particle is 0.5% to 35%.
2. The negative electrode active material according to claim 1, characterized in that The area percentage of the pores in a single secondary particle is 18% to 30%.
3. The negative electrode active material according to claim 1, characterized in that There are circular holes in the cross section of the second phase material, and the diameter of the circular holes is D1, where D1 satisfies: 45nm≤D1≤550nm; preferably, 55nm≤D1≤480nm.
4. The negative electrode active material according to claim 1, characterized in that The second phase material contains a first element; the first element includes any one of Li, Na, K, Rb, Mg, Ca, and Zn; the content of the first element relative to the total mass of the negative electrode active material is 0.01% to 1.2%; preferably, the content of the first element relative to the total mass of the negative electrode active material is 0.02% to 0.95%.
5. The negative electrode active material according to claim 1, characterized in that The negative electrode active material satisfies at least one of the following conditions (1) to (4): (1) The secondary particles have a coating layer on their surface, and the thickness of the coating layer on the secondary particles is in the range of 10 to 110 nm; preferably, the thickness of the coating layer on the secondary particles is in the range of 25 to 100 nm; (2) The particle size Dv50 of the first phase material is in the range of 1 μm ≤ Dv50 ≤ 10 μm; preferably, the particle size Dv50 of the first phase material is in the range of 2 μm ≤ Dv50 ≤ 5 μm; (3) The ID / IG value of the secondary particles is in the range of 0.4 to 1.2; (4) The compaction density of the negative electrode active material is in the range of 1.2 to 1.8 g / cc.
6. A method for preparing a negative electrode active material, characterized in that: include: The solid particles corresponding to the first phase material, the precursor corresponding to the second phase material, and the pore-forming agent containing the metal element are mixed, and the mixed system is spray-dried, carbonized, sieved, and washed in sequence, and then a coating layer is formed on the surface of the negative electrode active material by vapor deposition to obtain the negative electrode active material.
7. The preparation method according to claim 6, characterized in that: The solid particles corresponding to the first phase material include any one of natural graphite and artificial graphite; and / or, The precursor corresponding to the second phase material includes at least one of phenolic resin, resorcinol-formaldehyde resin, epoxy resin, cellulose or lignin; and / or, The pore-forming agent containing alkali metal elements includes at least one of LiOH, NaOH, KOH, RbOH, Mg(OH)2, Ca(OH)2, Zn(OH)2, K2CO3, Na2CO3, sodium carboxymethyl cellulose, and sodium lignin sulfonate; and / or, the spray drying temperature is T1, and the range of T1 is: 130°C to 230°C; and / or, The carbonization temperature is T2, and the range of T2 is: 600°C to 1000°C; and / or, The carbonization time is t1, and the range of t1 is: 1h~4h; and / or, The temperature of the vapor deposition is T3, and the range of T3 is: 700° C. to 1200° C.; and / or, The time of the vapor deposition is t2, and the range of t2 is: 0.5h~20h.
8. A secondary battery comprising a positive electrode sheet, a negative electrode sheet and an electrolyte, characterized in that: The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector, and the negative electrode active material layer includes the negative electrode active material described in any one of claims 1-5 or the negative electrode active material prepared by the preparation method described in any one of claims 6-7.
9. The secondary battery according to claim 8, characterized in that: The negative electrode sheet uses lithium metal as the counter electrode at 0 to 2.5V vs Li + In the capacity-voltage differential curve obtained by testing within the range of / Li, the charging curve has at least 4 characteristic peaks: F1, F2, F3, and F4, wherein F1 is located between 0.06 and 0.08V in the capacity-voltage differential curve, F2 is located between 0.09 and 0.12V in the capacity-voltage differential curve, F3 is located between 0.13 and 0.15V in the capacity-voltage differential curve, and F4 is located between 0.21 and 0.25V in the capacity-voltage differential curve; The peak intensity corresponding to F1 is C1, the peak intensity corresponding to F2 is C2, the peak intensity corresponding to F3 is C3, and the relationship between C1 and C2, C3 satisfies: 0.1≤C1 / C2≤1.0, 1≤C2 / C3≤20.
10. The secondary battery according to claim 8, characterized in that: The negative electrode sheet uses lithium metal as the counter electrode at 0 to 2.5V vs Li + In the capacity-voltage differential curve obtained by testing within the range of / Li, there are at least three characteristic peaks in the discharge curve: E1, E2, and E3, wherein E1 is located between 0.05 and 0.07 V in the capacity-voltage differential curve, E2 is located between 0.08 and 0.11 V in the capacity-voltage differential curve, and E3 is located between 0.16 and 0.20 V; the peak intensity corresponding to E1 is D1, the peak intensity corresponding to E2 is D2, and the relationship between D1 and D2 satisfies: 1.3≤D1 / D2≤3.
0.
11. An electronic device, characterized in that: The electronic device comprises the secondary battery as claimed in any one of claims 8 to 10.
Citation Information
Patent Citations
Negative active material, method for preparing same, secondary battery, and device comprising secondary battery
CN114223072A
Negative pole piece, secondary battery and electronic device
CN117393696A
Carbon negative electrode active material and preparation method thereof, secondary battery and electric device
CN118448629A
Porous carbon material as well as preparation method and application thereof
CN118702098A
Negative electrode active material, negative electrode piece, electrochemical apparatus, and electronic apparatus
WO2022178748A1